Exploring Local Perspectives for Conservation Planning: A Case Study from a Remote Forest Community in Indonesian Papua - Heist, M. van; Liswanti, N.; Boissiere, M.; Padmanaba, M.; Basuki, I.; Sheil, D. (MDPI, 2015)
Reconciling conservation and livelihoods is a concern wherever forests are important in local people’s lives. We plead for engaging these people in survey activities to clarify what is important to them, as a first step in conservation planning. This will help to address their priorities and gain their guidance and support for interventions. This paper presents the results of such a survey with the community of Kwerba in Mamberamo, a remote and little known part of Indonesian Papua. Views and priorities were explored through interviews, scoring exercises, community mapping and a field survey. Whereas small gardens provided most staple food, culture and livelihoods were linked to the forest. People scored primary forest highest for nearly all use categories. Primary forest was particularly highly valued as a source of construction materials, ornaments and rituals, and as a hunting place. We developed a list of the overall most important plants and animals. Many natural resources were used, but few were commercially exploited. The community had rules to control access to certain areas and resources. Taboos to restrict access to sacred places were also maintained. Our evaluation identified opportunities to achieve conservation outcomes jointly with the Kwerba people. In follow-up activities, the community presented local government with a land-use plan for their territory. The government recognized the value of our approach and requested training to implement it more widely in the region.